1999
DOI: 10.1161/01.atv.19.5.1276
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Modification of LDL by Phospholipase A 2 Induces Particle Aggregation in the Absence and Fusion in the Presence of Heparin

Abstract: Abstract-One of the first events in atherogenesis is modification of low density lipoprotein (LDL) particles in the arterial wall with ensuing formation of aggregated and fused lipid droplets. The accumulating particles are relatively depleted in phosphatidylcholine (PC). Recently, secretory phospholipase A 2 (PLA 2 ), an enzyme capable of hydrolyzing LDL PC into fatty acid and lysoPC molecules, has been found in atherosclerotic arteries. There is also evidence that both LDL and PLA 2 bind to the glycosaminogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…This was performed because lipolysis of LDL with PLA 2 in vitro induces particle aggregation. 22 The results from these studies showed that in vitro modification of recombinant LDL with PLA 2 gave similar results as in vivo modification of LDL, ie, binding affinity increased on PLA 2 digestion and site A was required for the increased interaction of sPLA 2 -modified LDL with glycosaminoglycans (data not shown). However, the intra-assay variations (ie, imprecision) and the inter-assay variations (ie, irreproducibility) were much more pronounced when analyzing the binding of LDL digested with PLA 2 in vitro compared with LDL modified in vivo.…”
Section: Solid-phase Assays Of Recombinant Ldl Isolated From Spla 2 Tmentioning
confidence: 85%
See 3 more Smart Citations
“…This was performed because lipolysis of LDL with PLA 2 in vitro induces particle aggregation. 22 The results from these studies showed that in vitro modification of recombinant LDL with PLA 2 gave similar results as in vivo modification of LDL, ie, binding affinity increased on PLA 2 digestion and site A was required for the increased interaction of sPLA 2 -modified LDL with glycosaminoglycans (data not shown). However, the intra-assay variations (ie, imprecision) and the inter-assay variations (ie, irreproducibility) were much more pronounced when analyzing the binding of LDL digested with PLA 2 in vitro compared with LDL modified in vivo.…”
Section: Solid-phase Assays Of Recombinant Ldl Isolated From Spla 2 Tmentioning
confidence: 85%
“…The reason for this was to achieve similar modification of LDL as in patients with increased plasma levels of sPLA 2 . 13 Prolonged digestion of LDL with PLA 2 in vitro results in hydrolysis of nearly all of the phosphatidylcholines, in pronounced aggregation, and in the presence of glycosaminoglycans fusion of LDL, 22 ie, the modifications of LDL that are more likely to occur within the extracellular matrix of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 This increase can be explained by the fact that LDL aggregates contain many copies of apoB-100, and, being multivalent, have the potential to interact with proteoglycans via more ionic interactions than their nonaggregated, native-sized counterparts. Interestingly, binding of LDL to proteoglycans promotes PLA 2 -induced aggregation and fusion of LDL particles, 22 and an enhanced interaction of sPLA 2 -V-treated LDL to proteoglycans has been demonstrated by Rosengren et al 15 In terms of atherogenesis, the full repertoire of the ApoB-100 -containing lipoproteins enter the arterial intima and become entrapped within the subendothelial proteoglycan meshwork. A subendothelially located macrophage synthesizes and secretes sPLA 2 -V, which hydrolyzes the phosphatidylcholines on the surface of the entrapped lipoproteins.…”
Section: See Page 600mentioning
confidence: 97%